Freshness-based real-time shelf-life estimation of packaged chicken meat under dynamic storage conditions. (28th August 2019) - Yimenu, Samuel Mezemir; Koo, Junemo; Kim, Byeong Sam; Kim, Jong Hoon; Kim, Ji Young
ABSTRACT: The current study was performed to develop dynamic quality and shelf-life prediction models using selected index for packaged chicken meat during storage. Generally, the results showed that meat deterioration, with respect to the different quality indices considered in the investigation, proceeds with increasing temperature and storage time. Highly significant ( P ≤ 0.01) correlations were obtained between TPC (total plate count) and SI (sensory index) (r = −0.94 to −0.97), coliforms and SI (r = −0.89 to −0.95), and LAB (lactic acid bacteria) and SI (r = −0.93 to −0.98). However, only the microbiological spoilage regarding TPC, whose values ranged from 7.0 to 8.0 log CFU/g under all investigated temperature conditions, were in compliance with the end of sensory shelf-life defined at SI = 5. To develop dynamic quality prediction model, 4 isothermal (0, 4, 10, and 15°C) experiments in 2 batches were performed for TPC evaluation. Growth data were fitted in the Baranyi and Roberts and quadratic polynomial model as the primary and secondary models, respectively. The model was validated under dynamic conditions (0–8°C scenario with periodic 12-h changes). The accuracy and bias factors were estimated to be 1.045 and 0.991 for fluctuating conditions and 1.016 and 1.015 for real-time conditions, respectively, suggesting good applicability of the model. The remaining shelf-life estimation model developed based on mean kinetic temperature showed an even decrease of shelf-life under dynamic conditions in time. The developed model scan can be used for effective monitoring of packaged chicken meat freshness and shelf-life during distribution with temperature fluctuation.